Review of Melolontha Fabricius, 1775 (Coleoptera: Scarabaeidae: Melolonthinae) from India with the description of two new species - Gupta, Devanshu; Keith, Denis; Bhunia, Debika; Das, Priyanka; Ghosh, Joyjit; Chandra, Kailash (Zootaxa, 2023)
The genus Melolontha Fabricius, 1775 (Coleoptera: Scarabaeidae: Melolonthinae) from India is reviewed. Two new species, Melolontha arunachalensis Gupta, Keith, Bhunia, Das, Ghosh & Chandra, new species and Melolontha lachungensis Gupta, Keith, Bhunia, Das, Ghosh & Chandra, new species are described. Melolontha chinensis Guérin-Méneville, 1838 is reported for the first time from India. Taxonomic notes on the identification of previously known species of Melolontha from India are provided, together with a key to the species (males).